Jumper : a day in the life of a backyard jumping spider - Lanan, Jessica (Roaring Brook Press, 2023)
"What if you were as small as a bean and could walk on the walls and ceiling, sense vibrations through your elbows, jump five times your body length, see the world through eight eyes, and hear using tiny hairs all over your body? That is Jumper's world. Open this book and discover the fascinating hidden life of a backyard jumping spider."--